2021
DOI: 10.3389/fpsyg.2021.648002
|View full text |Cite
|
Sign up to set email alerts
|

Communication Across Maternal Social Networks During England’s First National Lockdown and Its Association With Postnatal Depressive Symptoms

Abstract: Postnatal/postpartum depression (PND/PPD) had a pre-COVID-19 estimated prevalence ranging up to 23% in Europe, 33% in Australia, and 64% in America, and is detrimental to both mothers and their infants. Low social support is a key risk factor for developing PND. From an evolutionary perspective this is perhaps unsurprising, as humans evolved as cooperative childrearers, inherently reliant on social support to raise children. The coronavirus pandemic has created a situation in which support from social networks… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 117 publications
(150 reference statements)
3
41
0
2
Order By: Relevance
“…Given that increased uncertainty and anxiety was often attributed to a lack of supportive presence of both family, peers, and healthcare professionals, ensuring the established option of virtual support is more routinely available would seem to be an important building block in ensuring continuity of anti‐ and postnatal care going forward. Relatedly, Myers and Emmot ( 2021 ) found that mothers during the COVID‐19 pandemic who engaged in remote communication with a higher proportion of their social network experienced fewer depressive symptoms. However, they also found that mothers described virtual support as lacking the ability to respond to unanticipated problems.…”
Section: Discussionmentioning
confidence: 99%
“…Given that increased uncertainty and anxiety was often attributed to a lack of supportive presence of both family, peers, and healthcare professionals, ensuring the established option of virtual support is more routinely available would seem to be an important building block in ensuring continuity of anti‐ and postnatal care going forward. Relatedly, Myers and Emmot ( 2021 ) found that mothers during the COVID‐19 pandemic who engaged in remote communication with a higher proportion of their social network experienced fewer depressive symptoms. However, they also found that mothers described virtual support as lacking the ability to respond to unanticipated problems.…”
Section: Discussionmentioning
confidence: 99%
“…Myers and Emmott 28 noted that low levels of social support and social isolation increased a person’s risk for postpartum depression (PPD) among the perinatal population in England. They identified 3 main challenges contributing to higher rates of PPD during lockdown: decrease in support from others contributed to feeling overwhelmed by “constant mothering” and managing domestic tasks on their own.…”
Section: Covid’s Impact On Mental Health In the Perinatal Periodmentioning
confidence: 99%
“…Last, women reported sadness based on an inability to establish “mommy friends” due to the closing of classes for new parents. 28 …”
Section: Covid’s Impact On Mental Health In the Perinatal Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main strengths of HBE is that researchers can focus their areas of inquiry on those that are predicted by theory, which may lead to unexpected insights and reduce data-driven trial-and-error. For instance, HBE predicts that people will produce children even though children are immensely costly (Mace 2014), that people are willing to engage in dangerous or risky behavior if it is needed to attract a mate (Wang 2002), and that mental health will suffer if parents are isolated without help to raise children during a global pandemic (Myers and Emmott 2021). All of these can be empirically tested.…”
Section: Introductionmentioning
confidence: 99%